2004
DOI: 10.1016/s0002-9440(10)63767-4
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage/Microglial Accumulation and Proliferating Cell Nuclear Antigen Expression in the Central Nervous System in Human Immunodeficiency Virus Encephalopathy

Abstract: This study was performed to quantitate and characterize the mononuclear phagocytes (MPs) in human immunodeficiency virus encephalopathy (HIVE) by immunohistochemistry in an effort to gain insights into potential mechanisms of central nervous system (CNS) accumulation. Single-and double-labeled studies using antibodies against CD14, CD16, CD68, proliferating cell nuclear antigen (PCNA), Ki-67, von Willebrand factor, and HIV-1 p24 were performed using brain tissue from patients with HIVE, HIV-1 infection without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 44 publications
1
87
1
Order By: Relevance
“…In this respect, several lines of evidence ascribe an important role for C/EBPb in the efficient transcription and replication of HIV-1 in several cell types, particularly in cells of myeloid lineage which support HIV-1 replication in brain and play an important role in the neuropathogenesis of AIDS. [10][11][12][13][14][15][16] Examination of several clinical samples from AIDS patients with dementia revealed a distinct mutation in the C/EBPb-binding site of the LTR …”
Section: Resultsmentioning
confidence: 99%
“…In this respect, several lines of evidence ascribe an important role for C/EBPb in the efficient transcription and replication of HIV-1 in several cell types, particularly in cells of myeloid lineage which support HIV-1 replication in brain and play an important role in the neuropathogenesis of AIDS. [10][11][12][13][14][15][16] Examination of several clinical samples from AIDS patients with dementia revealed a distinct mutation in the C/EBPb-binding site of the LTR …”
Section: Resultsmentioning
confidence: 99%
“…Microglia have been shown to contribute to a number of human neurodegenerative diseases, including Alzheimer's, human immunodeficiency virus dementia, multiple sclerosis, and others (6,12,26). However, the role of activated microglia in retrovirus-induced animal models of neurodegeneration has been controversial (16,28).…”
Section: Discussionmentioning
confidence: 99%
“…59 Because we and others have shown that the majority of blood monocytes are CD163 positive, it is possible that CD163 ϩ cells reported by Fox and colleagues 40,49 are recent CNS immigrants. Rappaport and colleagues 8,60 have suggested that HIVinfected CD16 ϩ microglia in the CNS of patients with HIVE might be derived from monocytes that have recently trafficked to the CNS and lost CD14 expression. Our data partly underscore this possibility.…”
Section: Cd163 a Monocyte Lineagementioning
confidence: 99%